Use of organic fertilizer and biofertilizer on corn-soybean intercropping for silage production - Dzulkfli, Noorhanin (2017)
Continuous usage of chemical fertilizers contributes to environmental pollution. This awareness leads society to find alternative fertilizers like organic fertilizers and biofertilizers. In this regard, an experiment was conducted at Universiti Putra Malaysia in two seasons to determine the effects of different fertilizer on growth and yield of corn intercropped with soybean and nutritive quality of mixed forage and silage. Six fertilizer treatments with three replications were arranged in randomized complete block design. The treatments were 100%chemical fertilizer (NPK), 100%poultry manure (PM), 50% PM, combined application of 50% PM with biofertilizer, sole biofertilizer and untreated (control).The results showed that highest yield of corn and soybean was obtained from 100%NPK but in the second season, 100% PM produced similar yield with 100% NPK. Sole biofertilizer was capable of producing equal yield as 50% PM. However, the combined application of 50% PM with biofertilizer did not increase the yield to the same level as either 100% PM or 100% NPK in both seasons. In terms of forage quality, 100% PM and 100% NPK produced the highest crude protein (CP) content (14.57% and 14.31% respectively) but only 100% PM gave desirable values for neutral detergent fiber (NDF) (49.86%) and acid detergent fiber (ADF) (27.77%) compared to others. Nutritive quality of the corn-soybean silage reflected the original material properties before storage where 100% PM produced high value of CP with lowest values of NDF and ADF. Dry matter, pH and volatile fatty acids of silage were not significantly affected by fertilizer treatments. Another objective was to quantify the biological nitrogen fixation (BNF) by soybean intercropped with corn. Corn and soybean root samples were harvested at 30 days after planting and were prepared for acetylene reduction assay (ARA). The ARA result may reflect nitrogenase activity because nitrogenase responsible in reduction of molecular dinitrogen (N2) to ammonia (NH4+) and also in reduction of acetylene to ethylene. The results showed that high ARA rates for corn (12.73 nmol h⁻¹) and soybean (41.45 nmol h⁻¹) were obtained from treatments containing biofertilizer. Control plots also gave high ARA rate above 100% NPK, 100% PM and 50% PM. This indicates that BNF is increase in low nitrogen level condition and inhibited by high nitrogen level. Biofertilizer treatments did not improve the yield and quality of mixed forage and silage over 100% NPK or 100% PM. Therefore, 100% poultry manure at the rate of 6.3 t ha⁻¹ which equivalent to 140 kg N ha⁻¹ is recommended to produce high yield and quality of mixed forage and silage.